Prevention, precaution and resilience: Are they worth the cost?. (August 2021) - Ale, Ben J.M.; Hartford, Des N.D.; Slater, David H.
Highlights: The value of life is too uncertain for an ethically justified cost benefit analysis. Many corporations seem to take loss of life to be part of the cost of doing business. Resilience seems another step towards putting economy before people. Abstract: The assumption that risk, represented as an expected value of the loss could be implied to be a measure of safety, in a cost benefit analysis, is firmly entrenched in economic risk analysis. However, this does not mean that without a marker, the value of a loss, can be established with any necessary level of certainty to make such a cost balancing act ethically possible. The appropriateness of using the Value of a Statistical Life (VOSL) at all in a safety analysis, is a matter of perspective, which renders attempts to establish a uniform value of a statistical life questionable. This makes it questionable whether decisions from which values for a VOSL were evaluated, really were based on consideration of saving lives, or whether other arguments, such as available budget, were much more dominant. Ethical considerations do not seem to be in the frame of corporate risk management, where loss-of-life catastrophes appear to be simply the cost of doing business. Because there is no real basis for any estimate of the value of a statistical life, the values employed in cost-benefit analyses therefore only seem to serve the purpose of dissembling, concealing that the decision is taken on grounds other than saving human lives, or even that potential harm to humans was not even considered. The strict meaning given to resilience as at most to make a plan for recovery and see if we can live with the consequences, seems just another step towards putting the economy before people.